Revision of the plant bug genus Cylapocoris Carvalho (Hemiptera: Heteroptera: Miridae: Cylapinae), with descriptions of seven new species from Costa Rica, Brazil, Ecuador, and Venezuela - Wolski, Andrzej (Zootaxa, 2013)
The plant bug genus Cylapocoris Carvalho, 1954 is revised. Seven new species: Cylapocoris costaricaensis sp. nov., C. cucullatus sp. nov., C. fulvus sp. nov., C. laevigatus sp. nov., C. marmoreus sp. nov., C. plectipennis sp. nov., and C. simplex sp. nov. are described from Costa Rica, Brazil, Ecuador, and Venezuela. The genus Adcylapocoris Carvalho, 1989 is synonymized with Cylapocoris. Five species: C. castaneus (Carvalho, 1989), C. funebris (Distant, 1883), C. pilosus Carvalho, 1954, C. sulinus Carvalho & Gomes 1971, and C. tiquiensis Carvalho, 1954 are redescribed. Illustrations of the male genitalia, color pho-tographs of dorsal and lateral views of the adult of most species, scanning electron micrographs of selected structures of C. simplex, and keys to species of the genus Cylapocoris are provided.